Does Corporate Governance Amplify the Sustainability-Performance Link? Evidence from Indonesian Mining Companies - Deri Indriani; Herlin Tundjung Setijaningsih (Indonesian Journal of Taxation and Accounting, 2025)
This study aims to examine the influence of green accounting and environmental performance on financial performance in Indonesian mining companies and to analyze whether corporate governance strengthens these relationships. The study is motivated by the growing convergence between sustainability practices and corporate financial objectives, as well as inconsistent empirical findings in prior research regarding the relationship between environmental initiatives and firm profitability. Using a quantitative explanatory approach with a deductive hypothesis-testing design, this research analyzes panel data from 40 mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period, generating 200 firm-year observations. Data were obtained from annual reports, sustainability reports, and corporate governance reports, while environmental performance was measured using the PROPER rating issued by the Indonesian Ministry of Environment and Forestry. The analysis employed panel regression techniques using the Fixed Effect Model. The findings indicate that green accounting has a positive and significant effect on financial performance (β = 1.697, p < 0.01), while environmental performance demonstrates the strongest positive effect (β = 5.085, p < 0.01). Corporate governance also has a significant positive direct influence on financial performance (β = 1.683, p < 0.05) and strengthens the relationships between sustainability practices and financial outcomes through significant interaction effects between governance and both green accounting (β = 1.352, p < 0.05) and environmental performance (β = 0.231, p < 0.05). The results suggest that sustainability initiatives generate greater financial benefits when supported by effective governance mechanisms. However, the findings are limited to mining companies in Indonesia and may not be generalizable to other industries or institutional contexts. This study contributes to the sustainability accounting literature by integrating legitimacy theory and stakeholder theory with governance perspectives, highlighting corporate governance as an enabling mechanism that enhances the economic value of environmental practices in emerging market industries.